2015
DOI: 10.7747/jfes.2015.31.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Growth Analysis of Red Pine (Pinus densiflora) by Stem Analysis in the Eastern Region of Korea

Abstract: The study was performed to analyze the growth of the red pine (Pinus densiflora) in the Eastern Region of Korea.Stem profile data from a total of 8 dominant trees of which each tree represents its site were collected and used for the analysis. The stem volumes were calculated using Smalian's formula and much higher than the ones by Korea Forest Research Institute in larger than dbh 40 cm. The total bark volumes were more proportionally related to dbh and stem volume than to height and age. The bark thickness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…A study on another species (Pinus koraiensis) in S. Korea resulted in the way of growth percentages of DBH, height and volume tended to decrease with age particularly rapidly at age 20 -30 (Seo et al, 2014(Seo et al, , 2018. Likewise, in the eastern region of S. Korea the diameter and height growth of Pinus densiflora species felled down rapidly with longevity until age 30 (Seo et al, 2015). These indicate that tree growth pattern variation after maturation and changes through life time.…”
Section: Factors Influencing the Growth Patterns Of The C Obtusa Standsmentioning
confidence: 90%
“…A study on another species (Pinus koraiensis) in S. Korea resulted in the way of growth percentages of DBH, height and volume tended to decrease with age particularly rapidly at age 20 -30 (Seo et al, 2014(Seo et al, , 2018. Likewise, in the eastern region of S. Korea the diameter and height growth of Pinus densiflora species felled down rapidly with longevity until age 30 (Seo et al, 2015). These indicate that tree growth pattern variation after maturation and changes through life time.…”
Section: Factors Influencing the Growth Patterns Of The C Obtusa Standsmentioning
confidence: 90%
“…The sample tree, neither suppressed nor diseased, was cut at 0.2 m above the ground. From the fallen sample tree wood discs were collected at regular intervals, and the thickness of discs is 4 to 6 cm (Seo et al 2015).…”
Section: Data Collectionmentioning
confidence: 99%
“…Predictions of when, where, and how much timber may be harvested are necessary for effective harvest planning (Clutter and, Jones EP 1980;Prodan 1997). In order to effectively manage regrowth forests, formulate policies (Wykoff 1982), conduct strategic planning (Vanclay 1994) and manage operations, yield projections are unquestionably important (Seo et al 2015). Regression analysis, which is widely used in forestry to estimate weight scaling of saw logs (Bower 1962), rates of stem taper (Kozak et al 1969), biomass prediction (Edwards and McNab 1979), yield estimation (MacKinney and Chaiken 1939), and other factors, was used to create the majority of yield models.…”
Section: Introductionmentioning
confidence: 99%
“…saccharum(Dey et al 2017), Pinus densi ora(Seo et al 2015), Abies alba (Marziliano et al 2019) etc. In the yield study on Norway spruce at 40 years of age by Johansson (2014) also indicated that the tree yield increases with increase in diameter and age attained the yield up to 0.17 m 3 at 40 years.…”
mentioning
confidence: 99%